Hubungan Risiko Depresi Postpartum dengan Perkembangan Bayi USIA 3–12 Bulan Berdasarkan Kuesioner Pra-Skrining Perkembangan (KPSP) - Rahmi Andrita Yuda; Munawaroh Munawaroh; Dewi Susilawati; Dewi Suri Damayanti (Poltekkes Kemenkes Padang, 2025)
Maternal mental health in the postpartum period is a critical factor influencing infant development, especially during the First 1,000 Days of Life. Postpartum depression may impair caregiving quality and contribute to developmental delays in children. Objective: This study aimed to examine the relationship between maternal Edinburgh Postnatal Depression Scale (EPDS) scores and infant developmental outcomes based on the Developmental Pre-Screening Questionnaire (KPSP) among infants aged 3–12 months. A cross-sectional study was conducted among 85 mother–infant dyads attending Posyandu in East Jakarta. The EPDS was used to screen for postpartum depression, while KPSP assessed infant development. Data were analyzed using Pearson’s correlation. A total of 83.5% of mothers were at risk of postpartum depression (EPDS ≥10). Only 16.5% of infants showed age-appropriate development, while 56.5% were questionable and 27.1% showed developmental delays. There was a very strong and statistically significant negative correlation between EPDS scores and infant development scores (r = -0.962; p < 0.01). Conclusions: There is a significant association between postpartum depression and delayed infant development. Routine screening and community-based interventions are essential to integrate maternal mental health assessment with child development monitoring.